Mendelian randomization analysis and validation supports MEGF9 and MLLT11 as potential targets for the treatment of varicocele and male infertility - Cai, Bin; Sun, Dalin; Deng, Weimin; Jin, Yihan; Zhao, Hongle; Xing, Dong; Liu, Yuanyuan; Jin, Baofang (Frontiers in Endocrinology, 2024)
Objective：A growing body of research suggests a link between varicocele and male infertility (MI). However, current evidence is mainly based on retrospective studies, which are prone to interference from confounding factors and cannot establish causal relationships. Mendelian randomization (MR) studies on the causal relationship between varicocele and MI are very limited. Therefore, this study conducted a two-sample MR study to elucidate the causal effect between the two. Methods: Download the data set GSE216907 from the GEO database, and use R software to screen differential genes in normal and varicocele tissue samples. The drug targets of Bu Shen Huo Xue Prescription (BSHXP) were derived from the Herb database. All genetic datasets were obtained using publicly available summary statistics based on individuals of European ancestry from the IEU GWAS database. MR analysis was performed using MR Egger, weighted median (WM) and inverse variance weighted (IVW) to assess the causal relationship between exposure and outcome and to validate the findings by comprehensively evaluating the effects of pleiotropic effects and outliers. The renal vein constriction method was used to establish a pathological model of varicocele infertility. Results: MEGF9 and MLLT11, and were verified by molecular docking. MR analysis showed that MEGF9 was positively associated with MI (MR Egger, OR: 1.639, 95% CI: 1.124-2.391, P = 0.024; WM, OR: 1.235, 95% CI: 1.003-1.521, P = 0.047). MEGF9 is also positively associated with MI (IVW, OR: 1.35, 95% CI: 1.069-1.705, P = 0.012). Sensitivity analysis showed no heterogeneity and horizontal pleiotropy. The expression of MEGF9 and MLLT11 increased in the varicocele model group, while the expression decreased after treatment with low, medium, and high doses of BSHXP. In addition, the sperm number, motility, morphology, and fertility of rats in the model group were significantly lower than those in the control group (P<0.05). After BSHXP treatment, all indicators were significantly better than those of the model group (P<0.05). Conclusion: This study indirectly supports that varicocele causes MI. BSHXP inhibiting MEGF9 and MLLT11 may become a potential therapeutic target for alleviating varicocele and MI.